Characteristic of risk factor of thyroid cancer related metastatic bone disease at Sanglah General Hospital Denpasar between January 2013 to March 2019 - Nugraha, Gede Ketut Alit Satria; Wiratnaya, I. Gede Eka; Andika, Gde Dedy; Sunaria, Made (International Journal of Research in Medical Sciences, 2020)
Background: Metastatic bone disease (MBD) causes a massive morbidity, pain, and disability for the sufferers. Thyroid carcinoma, which is the most common endocrine cancer worldwide, also contributes to the increased rate of MBD, as 60% of patients with thyroid carcinoma experience bone metastasis. An urgency to further analyze the risk factors of bone metastasis in thyroid cancer is necessary in order to prevent and treat this unwanted occurrence earlier and better. Methods: A descriptive retrospective study was conducted using patients’s medical record data obtained from Sanglah General Hospital between January 2013 until March 2019. The variables obtained were sex, age, diagnosis, management, and fracture site. Results: There were 15 patients involved in this study, presenting with pathological fracture due to MBD from thyroid cancer. Ten patients were female (66.7%) and 5 were male (33.3%). According to the age group, 2 patients (13.3%) were <40 years old, 5 patients (33.3%) were >60 years old, while the majority of 8 patients (53.4%) were 40-60 years old. From the pathological result, 9 patients had follicular neoplasm (60%) and 5 patients had papillary neoplasm (33%). The most common site of metastasis was humerus in 7 patients (47%), while the other sites were femur, pelvic, and tibia. Conclusions: According to this series, there are several risk factors related to MBD from thyroid carcinoma, including female gender, the age of 40-60 years old, and follicular type neoplasm. A further study with bigger amount of sample is needed to improve the result.